Measuring the Effect of Kampong AMOI Program on Sustainability Factors using Social Return on Investment Method: A Case Study of Riding Panjang Village, Bangka Barat - Retno Suryani; Andriani Silfiana; Nurul Lathifah; Nurani Ikhlas (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
The Kampong AMOI (Integrated Agro-Independent) Program is a community empowerment program carried out by PT Timah Tbk Metallurgical Unit Muntok. This community empowerment was carried out in Riding Panjang Village, Merawang District, Bangka Regency, Air Putih Village, Tanjung Village, Muntok District, and West Bangka Regency. This program integrates three activities, namely nursery perennials, composting, and broiler cultivation. The Kampong AMOI program has a significant impact on the economic and environmental development of the three villages. Therefore, in this paper, the results of the program impact will be analyzed using the evaluative social return on investment (SROI) method. This study aims to comprehensively evaluate, measure, and calculate the impacts of the program's implementation from the environmental, economic, welfare, and social aspects. The Kampong AMOI Community Empowerment Program (Integrated Agro-Independent Village) results have an SROI value of 2.518. This result shows that every IDR 1 invested has a benefit or impact value of IDR 2.518. This result also concludes that the Kampong AMOI program is reasonable to be conducted in Riding Panjang Village, Air Putih Village, and Tanjung Village.